Efficient Expression of Acetylcholine-Binding Protein from Aplysia californica in Bac-to-Bac System. (20th July 2014) - Lin, Bo; Meng, Hailing; Bing, Hui; Zhangsun, Dongting; Luo, Sulan
Abstract : The Bac-to-Bac baculovirus expression system can efficiently produce recombinant proteins, but the system may have to be optimized to achieve high-level expression for different candidate proteins. We reported here the efficient expression of acetylcholine-binding proteins from sea hares Aplysia californica (Ac-AChBP) and a convenient method to monitor protein expression level in this expression system. Three key factors affecting expression of Ac-AChBP were optimized for maximizing the yield, which included the cell density, volume of the infecting baculovirus inoculums, and the culturing time of postinfection. We have found it to reach a high yield of ∼5 mg/L, which needs 55 h incubation after infection at the cell density of 2 × 10 6  cells/mL with an inoculum volume ratio of 1 : 100. The optimized expression system in this study was also applied for expressing another protein Ls-AChBP from Lymnaea stagnalis successfully. Therefore, this established method is helpful to produce high yields of AChBP proteins for X-ray crystallographic structural and functional studies.